: RESOURCE IDENTIFICATION IN GRID USING GRS (International Journal of Engineering and Computer Science, 2013)
One of the main success factors on which the grid computing depends is how quickly and correctly a computer is able to locate the resources like memory, CPU etc. in the Grid.  With the increase in the size of grid, this search can take a considerable amount of time which could degrade the application performance. In this paper we present a middleware Grid component, Grid Resource Software (GRS) that can be used by the end user system to identify the resources in lesser time.